Pushing the boundaries of accessibility – Governmental efforts on ensuring equal access to information to rural library users (1997–2007) - Máté Tóth (Netcom)
In 1997 a new Cultural Act was enacted which included, among other things, public library provision. Based on this act the Hungarian library system has been developed systematically through the consecutive strategic plans (Skaliczki, 1999). All projects aimed to push the boundaries of accessibility and to facilitate the realisation of the information society (Caidi, 2006). The 2003-2007 strategic period draws to an end and now we are able to review the tasks accomplished. (Skaliczki, 2003; 2006). The purpose of this article is to present an overview of the strategic development of Hungarian libraries between 1997 and 2007, and to draw up the basic figures regarding to this period. ()